The role of pH-metry in the diagnosis of vaginal infections - E F Kira; K E Semenova; A M Markarian (IP Berlin A.V., 2014)
The purpose of the study. Study the clinical significance of pH-metry for diagnosis of bacterial vaginosis (BV) and evaluate the optimal values of the normal micro ecology of the vagina. In addition, the objectives of the study included a comparative study of different methods and indicators of pH-metry. Materials and methods. 214 women aged 18 to 45 years (mean age 30,2±7,7 years) were examined, of which were formed two representative groups. The first group consisted of 114 patients with BV, the second - 100 healthy women selected in the comparison group. Each test was performed on six females pH measuring the different test methods or systems, only two groups - 1284 pH measurements. Comparison was made between foreign and domestic pH test strips on a new modification Colpe test pH.Results and discussion. In BV patients, the pH of the vagina on the measurement ionometers average equaled 6,49±0,07 and 6,24±0,034 depending on modelipriborov. In healthy women, vaginal pH content was within the average was 4,21±0,022 and 4,31±0,041 (p